Seed Fatty Acid Composition of Some Medicago L. and Melilotus L. (Fabaceae) Taxa From Turkey. Issue 2 (3rd March 2016) - Bakoglu, Adil; Kiliç, Ömer; Kökten, Kagan
Abstract: Fatty acids composition of plant oil of Medicago disciformis DC., Medicago orbicularis (L.) Bart., Medicago intertexta (L.) Mill var. ciliaris (L.) Heyn., Medicago scutellata (L.) Mill., Melilotus alba Desr. and Melilotus officinalis (L.) Desr. were analyzed. The fatty acid composition of these six different taxa were determined by gas chromatography. The fatty acid composition of plants used to this study showed different saturated and unsaturated fatty acid concentrations. The main fatty acids found were linoleic acid (19.43-56.25%), linolenic acid (22.10-36.35%), oleic acid (18.56-31.21%), stearic acid (3.16-5.09%) and palmitic acid (11.93-23.37%); while other fatty acids were found in minor proportions. As a result, present study determined that all taxa had the highest total unsaturated fatty acid amounts (69.81-82.53%) and the lowest total saturated fatty acid amounts (17.47-30.19%). The higgest unsaturated fatty acid determinated to Melilotus officinalis (82.53%), the lowest in Medicago intertexta (69.81%). In the study of species, palmitic and stearic acid were found, the major saturated fatty acids. The other hand oleic, linoleic and linolenic acids in major unsaturated fatty acids. Fatty acid composition of studied plants oils could be used as a chemotaxonomical marker.